The Effect of Land Conversion, Farmer Exchange Rate (NTP), Generation Crisis and Availability of Subsidized Fertilizers on Food Security Mediated by Sustainable Economy and Agricultural Labor Productivity - Wardania Toyyibah Putri Efendy; Evi Fitrotun Najiah; M. Yaskun (SEAN Institute, 2024)
This study aims to analyze the effect of land use conversion, farmers' terms of trade (NTP), generation crisis, and the availability of subsidized fertilizers on food security, mediated by sustainable economy and agricultural labor productivity, among farmers in Lamongan Regency. A quantitative approach was employed using SEM-PLS (SmartPLS 3.3.7) with a sample of 200 farmer respondents drawn from 20 villages in Sukodadi District, Lamongan. The outer model results confirm the validity and reliability of all constructs (outer loading >0.70, AVE >0.50, Composite Reliability >0.70). The inner model shows strong explanatory power for food security (R²=0.810). Key findings reveal that land use conversion has a significant negative effect on food security (β=−0.146, p=0.014) and on agricultural labor productivity (β=−0.256, p<0.001), while it positively affects the sustainable economy (β=0.354, p<0.001). The availability of subsidized fertilizers demonstrates the strongest positive effect on food security (β=0.911, p<0.001). Generation crisis positively influences food security (β=0.120, p=0.004) and agricultural labor productivity (β=0.292, p<0.001). Farmers' terms of trade do not significantly affect food security directly but positively impact agricultural labor productivity (β=0.811, p<0.001), through which indirect effects on food security are realized. Agricultural labor productivity significantly mediates the effects of land use conversion, farmers' terms of trade, and generation crisis on food security. The sustainable economy does not significantly mediate any of these relationships. These findings highlight the critical role of subsidized fertilizer policy and labor productivity enhancement in securing food resilience at the local level.